THINKING OF MORAL EDUCATION ACCORDING TO AL GHAZALI AND AL ZARNUJI PERSPECTIVE ON EPISTIMOLOGY AND AXIOLOGY - Rosidah, Umi; Nurhakim, Nurhakim; Khozin, Khozin (LP2M IAI Al-Khairat Pamekasan, 2024)
The aim of this research is to examine the thinking on moral education according to Al Ghazali and Al Zarnuji from the perspectives of ontology, epistemology, and axiology. In this research using qualitative methods and literature analysis, the results show that there are two figures who played a role in the development of moral education. Firstly, Imam Al Ghazali is one of the most popular scientists to date. He not only played a role in moral education, but he also formulated how it should be a teacher and student personality. In the practice of character education or moral education in schools today, Imam Al Ghazali's concept of moral education is still prevalent. The concept of moral education developed by Imam Al Ghazali is still used today because it is considered relevant to current conditions. Even though it is still relevant, it does not rule out the possibility that this concept also needs re-development to be more appropriate to the current situation where humans are faced with sophisticated technology. Therefore, it is important to maintain and advance moral education to prevent its extinction and replacement by something else. Second Imam Az Zarnuji in the book Ta'lim muta'alim About the study period; about mutual love and advice; taking knowledge; the state of studying; things that can strengthen memory and weaken it; things that can make it easier to bring in sustainability, prolong life, and reduce life.